Digital marketing and consumer behaviour of the Uber brand in Peru (LACCEI, 2024)
The main objective of this study was to determine how digital marketing influences the consumer behavior of the Uber brand, Lima Metropolitana 2021. In that sense, a non-experimental methodological design of cross-sectional, quantitative approach and explanatory level was used, considering as the study population the inhabitants of the city of Metropolitan Lima between the ages of 18 to 55 years old, considering a sample of 385 people. Therefore, the survey technique was used through the questionnaire as an instrument for measuring the variables, on an ordinal Likert-type scale, which presented a high level of overall internal consistency (Cronbach's alpha = .983) and content validity by expert judgment (Aiken's V = 1.00). It was concluded at a general level that digital marketing does significantly influence consumer behavior of the Uber brand, Lima Metropolitana 2021, demonstrated through Pearson's Chi-square inferential test, with a confidence level of 95% and a significance of 0.000, which confirms that consumer behavior of the Uber brand is explained by the possible actions or influence of digital marketing.